Does Gender Nonconforming Behavior in Early Childhood Predict Adolescents’ Depressive Symptoms? - Bennett, David S. (Sex Roles, 2019)
Gender nonconforming behavior (GNB) is a risk factor for poorer psychological adjustment, but little is known about whether preschool-age children displaying GNB are at risk for depressive symptoms during adolescence. We examined maternal report of GNB at age 4–5 years-old as a predictor of adolescents’ depressive symptoms at age 16–17 years-old in a longitudinal study of U.S. children from a predominantly low SES (61% received Aid to Families with Dependent Children) and African American (90%) sample. Youth with GNB in early childhood (n = 10) reported more depressive symptoms during adolescence than did their peers without GNB (n = 115), and this relationship remained after controlling for covariates (environmental risk, prenatal exposure, and neonatal medical problems). Our findings suggest that early GNB may be a risk factor for the development of depressive symptoms in adolescence. Further research is needed to replicate the current findings with a larger sample and to identify the underlying mechanisms by which GNB may increase risk for depressive symptoms. If replicated, the findings further highlight the need for both professionals and parents to become aware of the potential challenges that children with GNB face and to become knowledgeable about ways to facilitate healthy adjustment among gender nonconforming youth.